UJI MUTU BRIKET DARI PENCAMPURAN JERAMI DAN SEKAM PADI DARI LIMBAH PASCA PANEN DI LAHAN GAMBUT - Fonny Rianawati; Zainal Abidin; Muhammad Naparin (Jurnal Hutan Tropis, 2021)
This study aims to conduct a study of the quality value of briquettes made from mixing straw and rice husks which include a flame test and combustion rate which is expected to be used to educate people around the forest by providing innovation and technology regarding the use of post-harvest waste. The results showed that the value of the quality of briquettes made from variations in the mixing of straw and rice husks including the flame test of the combustion rate obtained results, for treatment A (100% straw) of 0.68 gr/minute, treatment B (100% husk) of 0 ,57 gr/minute, treatment C (Husk 75% + Straw 25%) was 0.40 gr/minute, treatment D (Husk 25% + Straw 75%) was 0.46 r/minute and treatment E (Husk 50% + Straw 50%) of 0.43 gr/minute. The value of the flame to boiling time for treatment A = 38.62 minutes, treatment B = 31.05, treatment C = 23.22 minutes, treatment D = 36.05 and treatment E = 27.95 minutes. Density values of all treatments, and the water content for treatment B and treatment C can meet SII. While other parameters: ash content, volatile matter, bound carbon and calorific value still cannot meet the standards, so it is recommended to carry out further research with other variations of treatment, in order to obtain briquettes with quality that can meet the standards.